What works for reducing stunting in low-income and middle-income countries? Cumulative learnings from the Global Stunting Exemplars Project - Bhutta, Zulfiqar A.; Islam, Muhammad; Gaffey, Michelle F.; Victora, Cesar G.; Menon, Purnima; Katz, Joanne; Horton, Susan E.; Yearwood, Jamal; Black, Robert E. (Elsevier, 2025)
Background Impaired linear growth and stunting in children under 5 y is a marker of multiple deprivations in low-income and middle-income countries. Objectives We aimed to assess drivers and policies influencing improvements in linear growth and stunting reduction in 10 countries with annual rates of reduction in childhood stunting averaging 1.1% (range: 0.4%–1.7%) at national-level or subnational-level, and to improve a framework of action for other countries to follow. Methods We used mixed methods to assess trends and patterns of improvement in linear growth in children under 5 y using available household-level data and in-depth analysis of programs and their implementation. We assessed patterns of change with multivariate regression analyses of risk factors driving stunting and affecting change. We compared results from the Oaxaca–Blinder decomposition analyses using a hierarchical approach and retrospectively assessed the appropriateness of a previously proposed 10-step process for country-level planning and implementation processes. Limited data precluded robust serial assessment of dietary intake at individual level for children and mothers. Results Rapid reduction in childhood stunting is possible and findings across exemplar countries underscore the benefits of indirect and direct interventions in health and other social sectors. These include programs focusing on poverty alleviation; water, sanitation, and hygiene; promotion of girls’ education and empowerment; and maternal nutrition. The potential benefits of family planning programs and factors contributing to gains in maternal nutrition were noted. In malarial endemic areas, malaria control programs were associated with improved childhood growth, and patterns of growth indicated continued benefits of childhood disease prevention and management strategies. Conclusions A systematic, evidence-informed approach to improve maternal and child health and nutrition is feasible and, with targeting, can accelerate reduction in linear growth faltering in childhood.